(untitled) (Scientia Agricola, 2011)
Seed priming with hormones has been an efficient method for increasing seed vigor as well as seedling growth under stressful conditions. These responses have in the past been attributed to the activation of antioxidant systems in a range of crops. The results described in this work show that hormonal priming with methyl jasmonate, salicylic acid or CEPA (chloroethylphosphonic acid), an ethylene (ET) releaser, does not induce the antioxidant activity of superoxide dismutase, catalase, ascorbate peroxidase or glutathione reductase in maize seedlings subjected to salt stress. The enhanced biomass of maize seedlings under salt stress that was observed only from ET priming indicates that the stress tolerance in maize from ethylene priming is a fundamental process for stress tolerance acquisition, which is explained, however, by other biochemical mechanisms but not by changes in the antioxidant system.